Women and Buddhism in East Asian history: The case of the Blood Bowl Sutra, Part II: Japan. Issue 4 (9th March 2020) - Meeks, Lori
Abstract: Part II turns to Japan, the other major East Asian region where beliefs and practices related to blood hells became commonplace, especially in the early modern period. This article traces Japanese reception of cults to the Blood Bowl Sutra, examining the particular ways in which blood hell cults developed there. As was the case in China, Japanese cults to the Blood Bowl Sutra often emphasized postmortem care for women and were disseminated largely through entertaining storytelling traditions. The cult also came to be associated, as it had been in China, with rites for safe childbirth. After examining the cults' historical development in Japan, this article will consider some of the larger insights made possible through a broadly conceived comparison of Chinese and Japanese cults to the blood hells.